Distribution, Abundance, Activity Patterns and Habitat Characteristics Associated with Family Herpestidae (Mammalia: Carnivora) in Three Protected Areas Representing Three Main Bioclimatic Regions of Sri Lanka - Jayasekara, E.G.D.P.; Mahaulpatha, W.A.D. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2019)
Four species of mongooses; Brown mongoose (Herpestes fuscus), Grey mongoose (H. edwardsii), Black-tipped/Ruddy mongoose (H. smithii) and Stripe-necked/Badger mongoose (H. vitticollis) belonging to the family Herpestidae are found in Sri Lanka. The distribution, abundance, activity and habitat characteristics of family Herpestidae was studied using camera traps in three protected areas (Horton Plains National Park-HPNP, MaduruOya National Park-MONP and Sinharaja Forest Reserve-SFR) that represent three of the six main bioclimatic regions of the island. Ruddy mongoose had the highest trap success (9.58, a measure of relative abundance) at MONP which was also the highest among all the species considered for any given study site. Interestingly, Stripe-necked mongoose was the most abundant in SFR with a trap success of 2.95. At each study site, there was a prominent species with a higher trap success followed by the remaining species with lower trap success rates. With a total of 143 mongoose sightings, MONP can be considered to be providing the suitable habitats for these animals with optimum conditions when compared to HPNP and SFR. Ruddy mongoose preferred habitats with higher rock availability while Stripe-necked mongoose preferred aquatic habitats. High leaf litter cover, litter depth and forested habitats with canopy cover were identified as important habitat characteristics that are associated with three observed Herpestids at MONP. Grey mongoose was absent in all camera trap records which suggests that habitat requirements of this species are not met within the study sites of focus. Data generated through this study can be incorporated for effective conservation and management measures in the future.
Keywords: Camera trapping, Mongooses, Meso-mammals, Relative abundance, Bioclimatic zones